2017
DOI: 10.1101/148320
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intercellular Communication via thecomX-Inducing Peptide (XIP) ofStreptococcus Mutans

Abstract: 21Gram-positive bacteria utilize exported peptides to coordinate genetic and physiological 41. CC-BY-NC-ND 4.0 International license It is made available under a was not peer-reviewed) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.The copyright holder for this preprint (which . http://dx.doi.org/10.1101/148320 doi: bioRxiv preprint first posted online Jun. 9, 2017; IMPORTANCE 42The comX-inducing peptide (XIP) of Streptococcus mutans is a key regulatory element … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 53 publications
(87 reference statements)
0
5
0
Order By: Relevance
“…Our working model must also account for the fact that XrpA fragments can elicit effects when provided exogenously. Therefore, we are testing the hypothesis that XrpA peptides, which may be released into the extracellular space through lysis, can be actively internalized, perhaps after processing, to elicit their effects on ComR – similar to what has been proposed for XIP (Kaspar et al ., ). Mass spectrometry studies are currently ongoing to localize XrpA and other S. mutans encoded peptides that affect competence (Ahn et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our working model must also account for the fact that XrpA fragments can elicit effects when provided exogenously. Therefore, we are testing the hypothesis that XrpA peptides, which may be released into the extracellular space through lysis, can be actively internalized, perhaps after processing, to elicit their effects on ComR – similar to what has been proposed for XIP (Kaspar et al ., ). Mass spectrometry studies are currently ongoing to localize XrpA and other S. mutans encoded peptides that affect competence (Ahn et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…XIP has been detected in culture supernates, supporting the hypothesis that XIP is a diffusible intercellular signal (Desai et al ., ; Khan et al ., ; Wenderska et al ., ), although the mechanism by which XIP is released into the environment can involve active transport (Chang and Federle, ) or cell lysis (Kaspar et al ., ), depending on the species of bacteria. Recently, it was confirmed experimentally that XIP is able to act as a diffusible intercellular communication molecule and that signaling can occur within biofilm populations (Shields and Burne, ; Kaspar et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…The model for XIP release and processing may differ in S. mutans . While three independent research groups have detected XIP in supernatant fluids of S. mutans (Desai et al, 2012; Khan et al, 2012; Wenderska et al, 2012), the mechanisms for secretion or processing have not been identified in this organism to date (Kaspar et al, 2017). Notably, in Streptococcus thermophilus (Gardan et al, 2013), the Eep protease processes ComS to XIP, but an equivalent function for proteases in S. mutans with characteristics similar to Eep has not been demonstrated (Khan et al, 2012).…”
Section: Bridging Comcde and Comrs—a Missed Connectionmentioning
confidence: 99%
“…This was in contrast to early biofilms (5–7 h), where robust comX activity was measured and the majority of the population responded. In a second study, a co-culturing system was designed such that one S. mutans strain (a “sender”) would overproduce the XIP peptide precursor ComS, exporting large amounts of XIP to the extracellular space so that a receiver strain, which was unable to produce XIP (Δ comS ), would internalize the XIP via the Opp transport system and a response could be measured (Kaspar et al, 2017). This study concluded that XIP had the potential to act as a diffusible signal and that the XIP released by a sender could activate a nearby responder in biofilm populations.…”
Section: Into the Milieu—are Peptide Signals Meant To Be Shared?mentioning
confidence: 99%
See 1 more Smart Citation